Co-Relation between Impacted Teeth and Odontogenic Cysts: Implication for Orthodontic Diagnosis - Faiza Rana, Abid Hussain Kanju, Taimur Khan, Usman Yousaf, Munawar Manzoor Ali, Saba Sikandar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: This study aimed to evaluate the correlation between impacted teeth and the presence of odontogenic cysts and to highlight key diagnostic considerations for orthodontic planning. Methods: A cross-sectional study was conducted at Frontier Medical and Dental College from January 2022 to December 2022. Seventy-one patients with radiographically confirmed impacted teeth were included. Data on age, gender, number and type of impacted teeth, jaw involvement, presence and type of cyst, and histopathological confirmation were collected. Chi-square test was applied to assess associations, with p ≤ 0.05 considered statistically significant. Results: Odontogenic cysts were identified in 60.6% of cases. A significant association was found between cyst presence and both the number of impacted teeth (p = 0.012) and the type of tooth involved, particularly mandibular third molars (p = 0.026). No significant correlation was noted with age, gender, or jaw site. Conclusion: Patients with multiple impacted teeth, especially mandibular third molars, are at increased risk of developing odontogenic cysts. Early radiographic assessment and appropriate referral are critical to prevent complications and to optimize orthodontic outcomes. Keywords: Impacted teeth, odontogenic cyst, mandibular third molar, dentigerous cyst, orthodontic diagnosis, radiographic evaluation